Functional annotation of rhizospheric phageome of the wild plant species Moringa oleifera - Ashy, Ruba A.; Jalal, Rewaa S.; Sonbol, Hana S.; Alqahtani, Mashael D.; Sefrji, Fatmah O.; Alshareef, Sahar A.; Alshehrei, Fatimah M.; Abuauf, Haneen W.; Baz, Lina; Tashkandi, Manal A.; Hakeem, Israa J.; Refai, Mohammed Y.; et al. (Frontiers in Microbiology, 2023)
Abstract The study aims to describe phageome of soil rhizosphere of M. oleifera in terms of the genes encoding CAZymes and other KEGG enzymes. Genes of the rhizospheric virome of the wild plant species Moringa oleifera were investigated for their ability to encode useful CAZymes and other KEGG (Kyoto Encyclopedia of Genes and Genomes) enzymes and to resist antibiotic resistance genes (ARGs) in the soil. Abundance of these genes was higher in the rhizospheric microbiome than in the bulk soil. Detected viral families include the plant viral family Potyviridae as well as the tailed bacteriophages of class Caudoviricetes that are mainly associated with bacterial genera Pseudomonas, Streptomyces and Mycobacterium. Viral CAZymes in this soil mainly belong to glycoside hydrolase (GH) families GH43 and GH23. Some of these CAZymes participate in a KEGG pathway with actions included debranching and degradation of hemicellulose. Other actions include biosynthesizing biopolymer of the bacterial cell wall and the layered cell wall structure of peptidoglycan. Other CAZymes promote plant physiological activities such as cell-cell recognition, embryogenesis and programmed cell death (PCD). Enzymes of other pathways help reduce the level of soil H2O2 and participate in the biosynthesis of glycine, malate, isoprenoids, as well as isoprene that protects plant from heat stress. Other enzymes act in promoting both the permeability of bacterial peroxisome membrane and carbon fixation in plants. Some enzymes participate in a balanced supply of dNTPs, successful DNA replication and mismatch repair during bacterial cell division. They also catalyze the release of signal peptides from bacterial membrane prolipoproteins. Phages with the most highly abundant antibiotic resistance genes (ARGs) transduce species of bacterial genera Pseudomonas, Streptomyces and Mycobacterium. Abundant mechanisms of antibiotic resistance in the rhizosphere include “antibiotic efflux pump” for ARGs soxR, OleC and MuxB, “antibiotic target alteration” for parY mutant, and “antibiotic inactivation” for arr-1. These ARGs can act synergistically to inhibit several antibiotics including tetracycline, penam, cephalosporin, rifamycins, aminocoumarin and oleandomycin. The study highlighted the issue of horizontal transfer of ARGs to clinical isolates and human gut microbiome.